Plasmin‐mediated proteolysis of human factor IXa in the presence of calcium/phospholipid: Conversion of procoagulant factor IXa to a fibrinolytic enhancer. (30th March 2020) - Schmidt, Amy E.; Vadivel, Kanagasabai; Whitelegge, Julian; Bajaj, Satya Paul
Abstract: Background: Factor (F) IX/IXa inactivation by plasmin has been studied; however, whether plasmin converts FIXa to a fibrinolytic enhancer is not known. Objective: Investigate plasmin proteolysis site(s) in FIXa that inactivates and transforms it into a fibrinolytic enhancer. Methods: NH2 ‐terminal sequencing, mass spectrometry analysis, and functional assays. Results: Plasmin in the presence of Ca 2+ /phospholipid (PL) rapidly cleaved FIXaβ at Lys316↓Gly317 to yield FIXaγ followed by a slow cleavage at Lys413↓Leu414 to yield FIXaδ. FIXaγ/FIXaδ migrated indistinguishably from FIXaβ in nondenaturing gel system indicating that C‐terminal residues 317‐415/317‐413 of heavy chain remain noncovalently associated with FIXaγ/FIXaδ. However, as compared with FIXaβ, FIXaγ or FIXaγ/FIXaδ (25‐75 mixture, 8‐hour/24‐hour incubation analysis by mass spectrometry) was impaired ~ 10‐fold in hydrolyzing synthetic substrate CBS 31.39 (CH3‐SO2‐D‐Leu‐Gly‐Arg‐pNA), ~ 30‐fold (~ 5‐fold higher K m, ~ 6‐fold lower k cat ) in activating FX in a system containing Ca 2+ /PL, and ~ 650‐fold in a system containing Ca 2+ /PL and FVIIIa. Further, FIXaγ or FIXaγ/FIXaδ bound FVIIIa with ~ 60‐fold reduced affinity compared with FIXaβ. Additionally, in ligand blots, plasminogen or diisopropylfluorophosphate‐inhibited plasmin (DIP‐plasmin) bound FIXaγ and FIXaδ but not FIXaβ. This interaction was prevented by ε‐aminocaproic acid or carboxypeptidase B treatment suggesting that plasminogen/DIP‐plasmin binds to FIXaγ/FIXaδ through newly generated C‐terminal Lys316 and Lys413. Importantly, FIXaγ/FIXaδ mixture but not FIXaγ enhanced tissue plasminogen activator (tPA)‐mediated plasminogen activation in a concentration dependent manner. Similarly, FIXaγ/FIXaδ mixture but not FIXaγ enhanced tPA‐induced clot lysis in FIX‐depleted plasma. Conclusion: Plasmin cleavage at Lys316↓Gly317 abrogates FIXaβ coagulant activity, whereas additional cleavage at Lys413↓Leu414 converts it into a fibrinolytic enhancer.